The translation of idioms from Indonesian into English in ziarah / Habizar - Habizar, Kincai (2016)

(untitled)
This research is aimed to investigate the strategies applied by the translator in translating the Indonesian idioms in novel “Ziarah” into its English target language text “The Pilgrim” and how effectively the meaning of the ST idioms conveyed to TT using the strategies identified. The objectives of this study are: (i) to analyze the strategies used in the translation of idioms in “Ziarah” from Indonesian into English, (ii) to find out if the meaning of the idioms is conveyed effectively using the strategies identified, and (iii) to describe the forms of idioms used in the TL text if the meaning of the idioms is conveyed effectively. In this study, the researcher employs Baker’s (2011) proposed strategies of translating idioms, Nida’s (1964) notion of equivalence in translation, as well as Makkai’s (1972) categorization of English idioms as the theoretical foundation for answering the three research questions of this study. Besides that, this study also classifies the Indonesian idioms into the three types of idioms, i.e pure idiom, semi idiom, and literal idiom, as proposed by Fernando (1996). Based on the results of this study, it was found that from the thirty three Indonesian idioms contained in the SL text, 45.15% of the extracted idioms are translated into English using the paraphrase stratgey; while 24.24% are translated by idiom of similar meaning but dissimilar form; 15.15% by idiom of similar meaning and form; 6.07% by omission of the entire idiom; and 9.09% are translated word for word. Moreover, the findings also reveal that the message that was considered as conveyed effectively into TT is 66.66% of the analyzed data; and less effectively conveyed in 21.21%; while the translated message was found to be distorted is only 12.12%. In terms of Makkai’s (1972) classification of English idioms, the findings of this study have shown that within the 22 (66.66%) of Indonesian idioms that are considered as effectively conveyed to TL text, 6 idioms were translated effectively into the forms of English “Phrasal Compounds Idiom”; 2 idioms were translated into the forms of “Tourneur iv Idioms”; 1 idiom was translated into the form of “Phrasal Verb Idioms”; and 13 idioms were translated effectively into the forms of English non-idiomatic expressions. This study has indicated that the most suitable strategy for conveying an inappropriate translated idiom is to use Baker’s (2011) strategy of translating an idiom by paraphrase.